2016
DOI: 10.1186/s12884-016-1018-5
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and timing of antenatal care among poor women in 6 Mesoamerican countries

Abstract: BackgroundPoor women in the developing world have a heightened need for antenatal care (ANC) but are often the least likely to attend it. This study examines factors associated with the number and timing of ANC visits for poor women in Guatemala, Honduras, Mexico, Nicaragua, Panama, and El Salvador.MethodsWe surveyed 8366 women regarding the ANC they attended for their most recent birth in the past two years. We conducted logistic regressions to examine demographic, household, and health characteristics associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Strategies to increase ANC contacts must target these women. Our findings were consistent with other studies [1,[24][25][26][27][28]: one of them examined coverage and timing of ANC among the poor in Mesoamerican countries and showed that education, parity and marital status were factors predicting timely ANC initiation [24]. Similarly, Gupta et al looked at utilization of antenatal care in Tanzania between 1990 and 2010 and found that urban residence, lower birth order and ANC initiation before four months of gestation were associated with utilization of at least four antenatal care visits [1].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Strategies to increase ANC contacts must target these women. Our findings were consistent with other studies [1,[24][25][26][27][28]: one of them examined coverage and timing of ANC among the poor in Mesoamerican countries and showed that education, parity and marital status were factors predicting timely ANC initiation [24]. Similarly, Gupta et al looked at utilization of antenatal care in Tanzania between 1990 and 2010 and found that urban residence, lower birth order and ANC initiation before four months of gestation were associated with utilization of at least four antenatal care visits [1].…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have also documented the high ANC performance in Latin America and Caribbean [23]: although this region has the largest income inequalities globally, with varying ANC performance across countries, programs targeting the most vulnerable such as performance-based contracts and conditional-cash transfer schemes have been successful at promoting ANC utilization in recent years [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, substantial progress has been made in the uptake of ANC, particularly in the MDG period (increased from only 1 in 4 women in 1990 to nearly 1 in 2 women in 2015) [ 5 ]. However, this is insufficient, as more than half of women living in LMICs do not receive any ANC during pregnancy, with significant within-country variations [ 6 10 ]. Consequently, around 303,000 maternal deaths, 2.6 million stillbirths, and 2.7 million newborn deaths occur in LMICs because of preventable causes related to pregnancy and childbirth [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subgroup analysis of these women across regions of countries found similar negative effects for sub-Saharan Africa and Latin America, while no effect was reported for Asia [ 21 ]. Conversely, country-level research in sub-Saharan Africa found highly inconsistent results with no [ 6 , 7 , 28 ] or negative effects of unintended pregnancy on ANC uptake [ 29 – 31 ]. Studies in Asian countries, including India and Bangladesh, found negative effects of unintended pregnancy on adequate (at least four visits) ANC [ 24 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Poor mothers and children start to fall behind their better-off peers in health-related consequences [7,8]. High rates of maternal and infant mortality and complications related to pregnancy can be minimized by referring to both preconception (before pregnancy) and interconception (between pregnancies) care [9,10]. Moreover, the risk of death or disability among infants can be prevented by healthy birth outcomes and prior identification and treatment of health-related problems.…”
Section: Introductionmentioning
confidence: 99%